The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1158/1535-7163.mct-13-1090
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Biomarkers Predictive of Response to PI3K Inhibitors and of Resistance Mechanisms in Head and Neck Squamous Cell Carcinoma

Abstract: The PI3K/AKT/mTOR pathway is frequently activated in head and neck squamous cell carcinoma (HNSCC), but pathway inhibition has variable efficacy. Identification of predictive biomarkers and mechanisms of resistance would allow selection of patients most likely to respond and novel therapeutic combinations. The purpose of this study was to extend recent discoveries regarding the PI3K/AKT/mTOR pathway in HNSCC by more broadly examining potential biomarkers of response, by examining pathway inhibitors with a dive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 50 publications
(78 reference statements)
6
80
1
Order By: Relevance
“…Such an approach was shown to be synergistic in head and neck squamous cell carcinoma cell lines. 41 It has been previously shown that somatic missense TP53 mutations cause nuclear accumulation of the TP53 protein, whereas truncated TP53 proteins resulting from frameshift mutations lead to the loss of TP53 protein. 42 Here, TP53 IHC was used to corroborate the TP53 sequencing findings.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach was shown to be synergistic in head and neck squamous cell carcinoma cell lines. 41 It has been previously shown that somatic missense TP53 mutations cause nuclear accumulation of the TP53 protein, whereas truncated TP53 proteins resulting from frameshift mutations lead to the loss of TP53 protein. 42 Here, TP53 IHC was used to corroborate the TP53 sequencing findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experience with other successful targeted agents in cancer suggests that clinical resistance to PI3K pathway inhibitors may reduce the durability of clinical benefit [76]. A recent study using reverse-phase protein arrays indicated that the activation of RTKs, including EGFR and ERK, commonly occurred following PI3K inhibition in SCCHN cells resistant to PI3K pathway inhibitors [77]. In addition, combined inhibition of PI3K and EGFR or MEK pathways showed synergistic activity.…”
Section: Blocking Pi3k Pathway and Other Pathways Concurrentlymentioning
confidence: 99%
“…The PI3K‐AKT‐mTOR signaling pathway is a vital pathway for growth, survival, and metabolism for which there is evidence of frequent functional signal activation in HNSCC cell lines and tumors 25, 26, 27, 28, 29. Genetic aberrations such as CNAs, mutations, and dysregulation of mRNA are prevalent.…”
Section: Resultsmentioning
confidence: 99%